Development of Artificial Intelligence Based Interactive Learning Media to Improve Students Understanding of Islamic Religious Education - Mavianti Mavianti; Rizka Harfiani; Suraiya Chapakiya; Abdurrahman Chapakiya (Fitrah: Journal of Islamic Education, 2026)
The rapid development of information technology has created new opportunities to enhance learning processes, yet Islamic Religious Education is often perceived as less engaging and less effective in improving students’ understanding. This study aims to develop an interactive learning media based on artificial intelligence to improve students’ comprehension in Islamic Religious Education at the junior secondary level. The study employed a research and development approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The developed media was validated by experts and tested through small and large group trials. The results indicate that the media achieved a very high level of feasibility, with expert validation scores of 92.5 percent for content and 88.7 percent for media design. Practicality tests showed that both teachers and students perceived the media as highly usable. Effectiveness testing revealed an increase in student understanding, with a normalized gain score of 0.58, categorized as moderate. These findings imply that artificial intelligence based interactive media can support more adaptive, engaging, and meaningful learning in Islamic education.